“The Word for Mercy” in the Church Slavonic Translation of the Second Half of the 17th Century and Its Polish Original: Realia Interpretation - Tatiana V. Pentkovskaya (Slovene, 2017)
“The Word for Mercy” was considered to be an original essay, written by Epiphanius Slavinetsky or Euthymius Chudovsky. In fact, it is a translation of Piotr Skarga’s cognominal sermon. The Church Slavonic translation is an example of the so-called inter-confessional rendering of the Polish original that shows its adaptation to the Orthodox tradition and to Russian historical and cultural specificity. The present paper analyses the problems of realia interpretation in the Church Slavonic translation of the Polish source. A distinctive feature of the translation is the elimination of specific signs of the Polish origin of the text. The translator pretends that a translated text is an original composition. To achieve this goal, he changes or omits the names of the Western saints. As markers indicating its place within the Byzantine tradition, he uses Greek lexical borrowings. Making a choice between lexical equivalents for transmission of the foreign realia, the translator probably uses multilingual lexicons such as the Thesaurus Polono-Latino-Graecus by Grzegorz Knapiusz and the Trilingual Lexicon by Epiphanius Slavinetsky. Very similar methods characterize the works of Simeon of Polotsk. Thus, it was not only the practice of the Chudov Monastery bookmen, but also Muscovite prevailing practice. “The Word for Mercy” is a unique example of adaptation of the Western ideas of state charity to the Russian situation in the second half of the 17th century. The ideological changes in the translation give this sermon features of the socio-legal project that is the hallmark of Early Modern times.